THE EXTENT OF MEDIAL QUADRICEPS TENDON FEMORAL LIGAMENT (MQTFL) PATELLAR AND QUADRICEPS ATTACHMENT: A PEDIATRIC CADAVERIC STUDY. Issue 7 (30th July 2021) - Stavinoha, Tyler J.; Randhawa, Sahej; Tompkins, Marc; Ellis, Henry; Ganley, Ted; Shea, Kevin G.
Background: The most common modern procedure for medial patellar stabilization involves reconstruction of the medial patellofemoral ligament (MPFL) and involves reconstructed ligament attachment to the femur and patella. However, cases of patellar fracture have been reported, particularly in the smaller anatomy of the pediatric population, leading to further investigations of patella stabilizing structures. The medial quadriceps tendon femoral ligament has been identified as a separate structure, connecting the patella to the femur and playing a significant role in patella stability. Reconstruction of this ligament may serve a role in patellar stabilization similar to pedicled quadriceps tendon medial ligamentous reconstructions. The anatomy and relationship of the MQTFL attachment to the quadriceps tendon and proximal pole of the patella has not been described in pediatric specimens. Purpose: To determine the anatomical relationship and attachment of the medial quadriceps tendon femoral ligament (MQTFL) on the patella and quadriceps tendon. Methods: Six pediatric cadaveric knee specimens were dissected to identify the patellar and quadriceps attachment site of the MQTFL. Dissection was facilitated by lateral arthrotomy and identification of the MQTFL thickened fibers from the undersurface of the ligament. Results: Six specimens included patients a mean age of 6 years at time of patient death (three 10-year-old specimens, one 4-year-old, and one 2-month-old specimen). The MQTFL was identified in all specimens. As identified from the undersurface of the everted extensor mechanism, it was found to insert a mean distance of 10.5 mm (range 3.9 – 18.2) from the superior pole of the patella. The attachment distally along the edge of the bony patella measured a mean of 12.7 mm (range 5.4-19.4). Total patellar length, as measured from the posterior articular surface, was a mean of 24.5 mm (range 11.0-35.6). Attachment to the quadriceps tendon averaged 47% of total attachment to both the quadriceps tendon and patella; conversely, direct patellar measurement averaged 53%. Conclusion: This study provides quantitative anatomy to attachment of the MQTFL to the patella and quadriceps tendon. Precise knowledge of these structures will assist to more precisely define the complex relationship between stabilizing structures to the medial patellofemoral joint and assist in patella stabilization procedures, particularly in skeletally immature patients. A lower risk of patellar fracture may be one of the key benefits of this procedure, compared with MPFL reconstruction. FIGURES: Figure 1:. View from the posterior surface (ie inside joint) following lateral arthrotomy. Note MQTFL attachment point in relation to the proximal extent of the cartilaginous articular surface. References: Fulkerson JP, Edgar C. Medial quadriceps tendon-femoral ligament: Surgical anatomy and reconstruction technique to prevent patella instability. Arthrosc Tech 2013;2:e125- e128. Joseph SM, Fulkerson JP. Medial Quadriceps Tendon Femoral Ligament Reconstruction Technique and Surgical Anatomy. Arthroscopy techniques. 2019 Jan 1;8(1):e57-64. Parikh SN, Wall EJ. Patellar fracture after medial patel- lofemoral ligament surgery: A report of five cases. J Bone Joint Surg Am 2011;93. e97(1-8) Dhinsa BS, Bhamra JS, James C, Dunnet W, Zahn H. Patella fracture after medial patellofemoral ligament reconstruction using suture anchors. Knee 2013;20:605- 608. Shah JN, Howard JS, Flanigan DC, Brophy RH, Carey JL, Lattermann C. A systematic review of complications and failures associated with medial patellofemoral ligament reconstruction for recurrent patellar dislocation. Am J Sports Med 2012;40:1916-1923 Tanaka MJ. The anatomy of the medial patellofemoral complex. Sports Med Arthrosc 2017;25:e8-e11. Kruckeberg BM, Chahla J, Moatshe G, et al. Quantitative and qualitative analysis of the medial patellar ligaments: An anatomic and radiographic study. Am J Sports Med 2017. 363546517729818 LaPrade RF, Engebretsen AH, Ly TV, Johansen S, Wentorf FA, Engebretsen L. The anatomy of the medial part of the knee. J Bone Joint Surg Am 2007;89:2000- 2010. Mochizuki T, Nimura A, Tateishi T, Yamaguchi K, Muneta T, Akita K. Anatomic study of the attachment of the medial patellofemoral ligament and its characteristic relationships to the vastus intermedius. Knee Surg Sports Traumatol Arthrosc 2013;21:305-310. Nelitz M, Williams SR. Anatomic reconstruction of the medial patellofemoral ligament in children and adolescents using a pedicled quadriceps tendon graft. Arthroscopy techniques. 2014 Apr 1;3(2):e303-8.